The naughtiest unicorn at Christmas - Bird , Pip; O'Connel, David (London, England Dean, 2021)
Pull on your Christmas jumper and untangle the tinsel! Its the week before Christmas and Mira and her friends are getting ready to celebrate the holidays with their unicorn best friends forever (UBFF)! Dave the naughtiest unicorn LOVES Christmas, mainly because there are so many delicious things to EAT. Plus there's a tree to decorate, a festive quest and a very special CHRISTMAS SHOW to rehearse. Mira is desperate for her and Dave to play the lead roles of Snow Unicorn and Lost Child . . . will her wish come true? Or will Dave get distracted by all the mince pies? One thing is for sure . . . Christmas time at Unicorn School is sure to be festive fun for EVERYONE!
English stories
Keywords: Christmas fiction; Christmas stories